Conducting the Needs Assessment #3: Educator Motivations, Barriers, and Objections - Matthew Benge (EDIS)
This third publication in the Conducting the Needs Assessment series outlines a range of motivations, barriers, and common objections Extension educators and other service providers may have pertaining to needs assessments. It is not an easy task to conduct a needs assessment, yet there are many motives for implementing one. This new 4-page publication of the Department of Agricultural Education and Communication discusses strategies for increasing educator motivation and removing barriers and objections to conducting a needs assessment. Written by Matt Benge. https://edis.ifas.ufl.edu/wc386